ALPHA-LIPOIC ACID IN TYPE 2 DIABETES MELLITUS: MECHANISMS, CLINICAL BENEFITS, AND IMPLEMENTATION IN THERAPY - DHARANI, B; SEBASTIAN, STEPHY; A, SUBA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Diabetes Mellitus (DM) encompasses a range of metabolic disorders marked by persistent high blood glucose levels. Type 2 Diabetes Mellitus (T2DM), the more common form of the disease is characterized by insulin resistance and partial insulin deficiency. The primary contributors to mortality and morbidity in diabetes are its vascular complications. Alpha-Lipoic Acid (ALA) is an antioxidant derived from caprylic acid and synthesized within the mitochondria. Extensive research shows that ALA aids in preventing and treating Diabetic Neuropathy (DN), lowers the risk of diabetes in at-risk individuals and is also beneficial for those with impaired glucose tolerance. Therefore, this review article aims to explore the different aspects of ALA and its beneficial effects on individuals with T2DM. A range of articles from databases such as Springer, Wiley, Web of Science, PubMed, Google Scholar, SCOPUS, Embase and Cochrane were examined. References from these articles were also analysed to broaden the search for pertinent reviews. Administering ALA in T2DM was found to have beneficial effects like anti-oxidant, anti-inflammatory, enhance glucose uptake, prevents diabetic neuropathy, neuroprotective, anti-obesity, cardio-protective, reno-protective, prevent diabetic retinopathy, anti-aging and improve metabolic parameters in Polycystic Ovary Syndrome (PCOS). Incorporating ALA into a comprehensive treatment plan, combined with lifestyle changes and standard therapies could improve patient outcome and enhance the quality of life for those managing T2DM and related conditions.